2016
DOI: 10.4049/jimmunol.1600893
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Targeting to Human HLA Class II Molecules Increases Efficacy of DNA Vaccination

Abstract: It has been difficult to translate promising results from DNA vaccination in mice to larger animals and humans. Previously, DNA vaccines encoding proteins that target Ag to MHC class II (MHC-II) molecules on APCs have been shown to induce rapid, enhanced, and long-lasting Ag-specific Ab titers in mice. In this study, we describe two novel DNA vaccines that as proteins target HLA class II (HLA-II) molecules. These vaccine proteins cross-react with MHC-II molecules in several species of larger mammals. When test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 45 publications
(88 reference statements)
1
56
0
Order By: Relevance
“…Supporting such a view, the selective induction of IgG2a and Th1 responses induced by Xcl1 vaccines [(19, 21), results in this study] could be due to the exclusive expression of the Xcr1 receptor on cross-presenting cDC1 cells (28,29). By contrast, aMHCII-vaccine proteins most likely target many different types of MHCII + APCs, perhaps explaining induction of a mixed IgG1/ IgG2a response as well as a Th1/Th2 profile [ (8,13,30), results in this study]. Similarly, aCD11c and Flt3 vaccine proteins should target both cDC1 and cDC2, contributing to the observed mixed IgG1/IgG2a responses (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 69%
“…Supporting such a view, the selective induction of IgG2a and Th1 responses induced by Xcl1 vaccines [(19, 21), results in this study] could be due to the exclusive expression of the Xcr1 receptor on cross-presenting cDC1 cells (28,29). By contrast, aMHCII-vaccine proteins most likely target many different types of MHCII + APCs, perhaps explaining induction of a mixed IgG1/ IgG2a response as well as a Th1/Th2 profile [ (8,13,30), results in this study]. Similarly, aCD11c and Flt3 vaccine proteins should target both cDC1 and cDC2, contributing to the observed mixed IgG1/IgG2a responses (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 69%
“…We have previously demonstrated that targeting of HA from H1N1 influenza viruses to MHCII molecules rapidly induced protective levels of neutralizing Abs in mice (18) and larger animals (21) and that APC-targeted DNA vaccines could be produced within 1 mo after identification of the viral sequence (28). In this article, we have demonstrated that this versatile and flexible format also contributed to improved Ab responses when extended to a mixture of six subtypes of influenza (H5, H6, H8, H9, H11, and H13).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the vaccine strategy could also confer some basic protection against an unexpected influenza emergence. To translate these results to humans, we have recently developed a targeting unit that is pan-specific for HLA class II molecules; this targeting unit should allow delivery of vaccine Ag to HLA class II molecules on APCs in all humans (21). Thus, the strategy presented in this article could be adapted to a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations